Post-operative necrotizing infection of the abdominal wall: con especial referencia a su diagnóstico y tratamiento - Carriquiry, Guillermo; Beguiristain, Alberto; Lago, Fernando; González, Jorge; Pérez Billi, Luis E (Cirugía del Uruguay, 1984)
By presentation of two clinical cases, the authors analyse post-operativa necrotizing infecions of abdo• minal wall, basically, in what concerns their diagnosis and treatment. They highlight the evaluation of the systemic consequences, a correct anatomo-lesional survey and prompt etiological orientation. The main point is antibiotic therapy and exceresis by emergency surgical treatment. The use of a mesh in the closing of the abdomen offers unquestionable advantages.